Lymphohistiocytic nodules caused by luetic infection - Pallavi Khattar, MD; Wenbin Xiao, MD PhD (Elsevier, 2018)
The histological diagnosis of luetic lymphadenitis remains challenging for the pathologists particularly when the pertinent clinical information is lacking. Here we report a case of a 23-year-old male, an immigrant from South America, who had a history of epithelioid hemangioma, presented with a painless enlarged left inguinal lymph node. In addition to the characteristic follicular hyperplasia and capsular thickening, lymphohistiocytic nodules are also seen. Recognition of such rare nodular proliferation can be helpful in diagnosing luetic lymphadenitis.